PERBANDINGAN MODEL PROJECT BASED LEARNING DAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XI SMA KATOLIK KARITAS TOMOHON - Tamboto, Henry; Siswanto, Sri Purwaningsi; Yalin, Stenli Wijayanto (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to find out the difference in learning outcomes using the Project Based Learning Model and the Discovery Learning Model in improving the economic learning outcomes of grade XI students of Karitas Tomohon Catholic High School. The method used in this research is an experimental research method with a Pre-test Post-test Control Group Design research design. The sample in this study was 60 students consisting of class XI A as experimental class 1 using the Project Based Learning Model totaling 30 students and class XI C as experimental class 2 using the Discovery Learning Model totaling 30 students. The results of the study with hypothesis testing using the Independent Sample T-Test showed a Sig. (2-tailed) value of 0,023 < 0,05. then as the basis for decision-making in the Independent Sample T-Test, it can be concluded that H0 is rejected and Ha is accepted. As for the value of tcalculated > ttable of 2,337 > 2,001, it can be concluded that H0 is rejected and Ha is accepted. Thus, there is a difference in learning outcomes using the Project Based Learning Model and the Discovery Learning Model in improving the economic learning outcomes of grade XI students of Karitas Tomohon Catholic High School. Keywords: Comparison, Project Based Learning, Discovery Learning, Learning Outcomes